Tanatological reception of the motif of love in Antique "text": two versions by Guy de Maupassant - Гальчук, Оксана Василівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article examines the connection between the traditional for Guy de Maupassant theme of Eros-Thanatos and the Antique "text" that is implicitly represented in mythologemes and philosophemes. The short stories The Graveyard Sisterhood and The Dead Girl incorporate a characteristic for modernism interpretation of the motive "love-death" as an ambivalent one; and offer the author's review of the mythologemes and ideological concepts of modernism rooted in the philosophical ideas of Antiquity. The study considers Maupassant’s short stories as neo-mythological texts, where the cosmological myth of the classical era is transformed into a social myth, and through the imposition of the space of life on the space of death is complemented by the motive of total – spatial, temporal, physical and ideological – deformation and author's myth of "useless beauty".These short stories embody author's tragic philosophical-symbolic (The Dead Girl) and ironically-frivolous (The Graveyard Sisterhood) versions of the traditional thematic connection, in which the motive of love is transformed into the "love for sale", expanded on the background of the cemetery-stage as an image of the modern world, where for the character, Orpheus, the "ascension to Hades" gets a new meaning.